delihusada Sosialisasi Kalibrasi Alat Kesehatan Dan Keselamatan Kerja Radiasi Di Bagian Radiologi Rumah Sakit Umum Sembiring Delitua Tahun 2021 - Depi Lianto; Julia Anatasya Yustan Efendi (LLPM Universitas Deli Sumatera, 2024)
Calibration is an activity to determine the correct value of the designation of measuring instrument and measuring materials. Rasiology Instalation ia one of the supporting specialist medical services in the hospital. This radiology utilizes X Ray for diagnostic purpose.Xray are a Type of ionizing radiation who, radiation exposure can be only provide benefits but can also cause harm. To present this can be done by implementing aspect of radiation safety management. This counseling to determine the implementation of medical device callibration and radiation safety in the radiology department of RSU sembiring. This type of research uses descriptive qualitatif methode with observation and interview data collection techniques. The result of this study indicate that the callibration of radiology medical device has been implemented and the implementation of radiation safety on management requiment, radiation protection requirement, building facilities and safety verification has not fully met the requirement. The recomended suggestions are the procurement of survey meters, the creatiob of emergency exposure management plans, training of radiation officers and consistent use of protective equiment